Magister amoris the Roman de la rose and vernacular hermeneutics - Minnis, A. J. (Alastair J.) (Oxford University Press, 2001)
The 13th century poem, The Roman de la Rose was a bestseller largely due to its robust treatment of natural sexuality. This study concentrates on the ways in which Jean de Meung, in imitation of Ovid, assumed the mock-mastership of love.